Balzac e os mitos da modernidade: Fausto e Don Juan em La peau de chagrin et L'elixir de longue vie - Santos, Marli Cardoso dos [UNESP] (2015)
The approach to the myths of modernity is a very comprehensive theme in Literary Studies. Fausto, Don Juan and Don Quixote are just a few examples of characters who become literature's representations of modern individuality. Over the centuries, a lot of variations of these myths illustrated the works of several writers, one of the reasons that enabled the spread of these figures. So we find in French literature, specifically the work of Honoré de Balzac, issues related not only to social but also to the individual, the man's nature. This way, the character Don Juan Belvidero, the story L'Elixir de longue vie, becomes one of the most satanic variations of the myth of Don Juan, since the selfish and ambitious caracter's behavior motivate his fall . Valentin Raphaël, protagonist of La peau de chagrin, can be then the representation of Fausto, who allied with Mephistopheles in exchange for power. However, Raphael is just a guy who haven't anything in life and gets the chance to own everything he ever desired, using a magic talisman, and the only disadvantage is to give his life in exchanged. We will analyze these two narratives to verify the construction of these characters, both founded in the myth of Fausto and Don Juan and for this it's necessary to rescue some variations of these figures in literary history to this work. Discoursing about these modern themes in Balzac's work is important from the critical fortune developed by Ernest Curtius, Pierre Brunel and other researchers of the Balzac's liteture, to go deep in our work and to develop the themes related to religion, modernity and power relations. Later, wil be necessary to analyze the narratives by their spatial and narratological features, with the help of Michel Foucault and Gérard Genette, so we can also understand if the magical objects appereance in narratives are related to the introduction of modern myths. The Theoretical Ian Watt, Jean Rousset, Pierre Brunel and...